Axonal Injury Partially Mediates Associations Between Increased Left Ventricular Mass Index and White Matter Damage. Issue 3 (27th October 2021) - Moore, Elizabeth E.; Khan, Omair A.; Shashikumar, Niranjana; Pechman, Kimberly R.; Liu, Dandan; Bell, Susan P.; Nair, Sangeeta; Terry, James G.; Gifford, Katherine A.; Anderson, Adam W.; Landman, Bennett A.; Blennow, Kaj; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Left ventricular (LV) mass index is a marker of subclinical LV remodeling that relates to white matter damage in aging, but molecular pathways underlying this association are unknown. This study assessed if LV mass index related to cerebrospinal fluid (CSF) biomarkers of microglial activation (sTREM2 [soluble triggering receptor expressed on myeloid cells 2]), axonal injury (NFL [neurofilament light]), neurodegeneration (total-tau), and amyloid-β, and whether these biomarkers partially accounted for associations between increased LV mass index and white matter damage. We hypothesized higher LV mass index would relate to greater CSF biomarker levels, and these pathologies would partially mediate associations with cerebral white matter microstructure. Methods: Vanderbilt Memory and Aging Project participants who underwent cardiac magnetic resonance, lumbar puncture, and diffusion tensor imaging (n=142, 72±6 years, 37% mild cognitive impairment [MCI], 32% APOE -ε4 positive, LV mass index 51.4±8.1 g/m 2, NFL 1070±588 pg/mL) were included. Linear regressions and voxel-wise analyses related LV mass index to each biomarker and diffusion tensor imaging metrics, respectively. Follow-up models assessed interactions with MCI and APOE -ε 4 . In models where LV mass index significantly related to a biomarker and white matter microstructure, we assessed if the biomarker mediated white matter associations. Results: Among all participants, LV mass index was unrelated to CSF biomarkers ( P >0.33). LV mass index interacted with MCI ( P =0.01), such that higher LV mass index related to increased NFL among MCI participants. Associations were also present among APOE -ε4 carriers ( P =0.02). NFL partially mediated up to 13% of the effect of increased LV mass index on white matter damage. Conclusions: Subclinical cardiovascular remodeling, measured as an increase in LV mass index, is associated with neuroaxonal degeneration among individuals with MCI and APOE -ε4. Neuroaxonal degeneration partially reflects associations between higher LV mass index and white matter damage. Findings highlight neuroaxonal degeneration, rather than amyloidosis or microglia, may be more relevant in pathways between structural cardiovascular remodeling and white matter damage.